Acute pulmonary non-cardiogenic edema after extubation with laryngospasm: a case report - Granados-Romero, Juan J.; Valderrama-Treviño, Alan I.; Arauz-Peña, Gerardo; Alcazar-Castro, Javier; Mendoza-Barrera, German E.; Banegas-Ruiz, Rodrigo; Barrea-Mera, Baltazar (International Journal of Research in Medical Sciences, 2018)
Acute pulmonary edema post extubation due to negative pressure with laryngospasm in the early postoperative period has been reported and may occur at any time during anesthesia. The usual treatment consists of respiratory support and diuretics. We present the clinical case of a 15-year-old patient who underwent laparoscopic appendectomy, who presented acute non-cardiogenic pulmonary edema in the postoperative period. This complication can be presented in any surgical patient intubated, so it is important to know the pathophysiological basis to be able to diagnose and treat this pathology.